Neutron Activation Cross Section Measurement of the (n,2n) Reaction on $^{203}$Tl at 14.6 MeV - Giannakou, Nikoletta; Bari, Zoe; Vlastou, Roza; Nicolis, Nikolaos; Pouris, Nikos; Kokkoris, Michael; Diakaki, Mary; Axiotis, Michail; Lagoyiannis, Anastasios (HNPS Advances in Nuclear Physics, 2026)
In the present work an experimental measurement of the 203Tl(n,2n)202Tl reaction cross section is presented, at the incident energy En,lab = 14.6 MeV, using the activation technique, relative to the reference reaction 27Al(n,a)24Na. The experiment took place at the 5.5 MV TANDEM Van de Graaff accelerator of N.C.S.R. “Demokritos”, and the neutron beam was produced via the 3H(d,n)4He reaction. The foils were irradiated under an 80◦ angle. A BF3 detector was utilized to monitor the neutron flux during the irradiation. The irradiated foils were placed in front of HPGe detectors to measure the induced activity by gamma-ray spectroscopy. The neutron fluence was simulated using the MCNP software.